Functional correlates of likelihood and prior representations in a virtual distance task. Issue 9 (11th May 2016) - Wiener, Martin; Michaelis, Kelly; Thompson, James C.
Abstract: Spatial navigation is an imperative cognitive function, in which individuals must interact with their environment in order to accurately reach a destination. Previous research has demonstrated that, when traveling a predetermined distance, humans must balance between noise in the measurement process and the prior history of traveled distances. This tradeoff has recently been formally described using Bayesian estimation; however, the neural correlates of Bayesian estimation during distance reproduction have yet to be investigated. Here, human subjects performed a virtual reality distance reproduction task during functional Magnetic Resonance Imaging (fMRI), in which they were required to reproduce various traveled distances in the absence of overt navigational cues. As previously demonstrated, subjects exhibited a central tendency effect, wherein reproduced distances gravitated to the mean of the stimulus set. fMRI activity during this task revealed distance‐sensitive activity in a network of regions, including prefrontal and hippocampal regions. Using a computational index of central tendency, we found that activity in the retrosplenial cortex, a region highly implicated in spatial navigation, negatively covaried between subjects with the degree of central tendency observed; conversely, we found that activity in the anterior hippocampus/amygdala complex was positively correlated with the central tendency effect of gravitating to the average reproduced distance. These findings suggest dissociable roles for the retrosplenial cortex and hippocampal complex during distance reproduction, with both regions coordinating with the prefrontal cortex the influence of prior history of the environment with present experience. Hum Brain Mapp 37:3172–3187, 2016 . ©2016 Wiley Periodicals, Inc.